Analisis terhadap Kriteria Muallaf sebagai Penerima Zakat di Baznas Kabupaten Purwakarta Menurut Peraturan Baznas No. 3 Tahun 2018 dan Persfektif Hukum Islam - Eka Tias Pratiwi; Amrullah Hayatudin; Iwan Permana (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Zakat is a certain property that must be issued by Muslims and given to those who are entitled to receive it. The group that is entitled to receive zakat there are eight, one of which is the convert. In BAZNAS Purwakarta Regency, to give zakat to converts must have criteria that have been set by BAZNAS.The problem is; How the process of distributing zakat distribution to converts in BAZNAS Purwakarta Regency, how to analyze the criteria of converts according to BAZNAS regulation No. 3 of 2018, how to analyze converts as zakat recipients according to the effectiveness of Islamic Law. The purpose of this study is to find out how the process of distributing zakat funds to the criteria of converts that have been established in accordance with BAZNAS N0 regulation 3 of 2018 and effective Islamic Law. The research methods used are descriptive with a qualitative approach. With primary and secondary data sources. Data collection techniques interviews documents and literature studies . The result of this study is that the criteria for converts in BAZNAS Purwakarta Regency have been in accordance with BAZNAS regulation No. 3 of 2018 and the distribution of zakat to converts is allowed according to the effectiveness of Islamic law. But zakat funds given to converts in BAZNAS Purwakarta can not be said to be able to prosper converts because the average assistance is consumptive. Abstrak. Zakat adalah harta tertentu yang wajib dikeluarkan oleh orang Islam dan diberikan kepada golongan yang berhak menerimanya. Golongan yang berhak menerima zakat ada delapan, salah satunya adalah golongan muallaf. Di BAZNAS Kabupaten purwakarta, Untuk memberikan zakat kepada muallaf harus memiliki kriteria yang telah ditetapkan oleh BAZNAS. Rumusan masalahnya yaitu; Bagaimana proses penyaluran distribusi zakat kepada muallaf di BAZNAS Kabupaten Purwakarta, bagaimana analisis terhadap kriteria muallaf menurut peraturan BAZNAS No 3 Tahun 2018, bagaimana analisis terhadap muallaf sebagai penerima zakat menurut persfektif Hukum Islam. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana proses penyaluran dana zakat kepada kriteria muallaf yang telah ditetapkan sesuai peraturan BAZNAS N0 3 Tahun 2018 dan persfektif Hukum Islam. Metode penelitian yang digunakan yaitu deskriptif dengan pendekatan kualitatif. Dengan sumber data primer dan sekunder. Teknik pengumpulan data yaitu wawancara, dokumentasi dan studi kepustakaan. Hasil dari penelitian ini adalah Kriteria muallaf di BAZNAS Kabupaten Purwakarta telah sesuai dengan peraturan BAZNAS No 3 Tahun 2018 dan Pembagian zakat kepada muallaf diperbolehkan menurut persfektif hukum Islam. Namun dana zakat yang diberikan kepada muallaf di BAZNAS Purwakarta belum bisa dikatakan dapat mensejahterakan muallaf karena rata-rata bantuan bersifat konsumtif